2000
DOI: 10.3201/eid0604.000401
|View full text |Cite
|
Sign up to set email alerts
|

Migratory Birds and Spread of West Nile Virus in the Western Hemisphere

Abstract: Disease Control and Prevention, or the authors' affiliated institutions. Use of trade names is for identification only and does not imply endorsement by any of the groups named above.All material published in Emerging Infectious Diseases is in the public domain and may be used and reprinted without special permission; proper citation, however, is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
350
0
15

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(370 citation statements)
references
References 16 publications
5
350
0
15
Order By: Relevance
“…Avian migration plays an important but little-studied role in the potentially rapid spread of microorganisms from the site of initial acquitision [24]. Understanding how migration affects the composition of the microbial community in the plumage and how this community changes throughout a migrant's annual cycle may provide important insights into microbial dispersal by birds.…”
Section: Discussionmentioning
confidence: 99%
“…Avian migration plays an important but little-studied role in the potentially rapid spread of microorganisms from the site of initial acquitision [24]. Understanding how migration affects the composition of the microbial community in the plumage and how this community changes throughout a migrant's annual cycle may provide important insights into microbial dispersal by birds.…”
Section: Discussionmentioning
confidence: 99%
“…When indicated, the labeled bands were excised from dried gels and quantified by liquid scintillation counting and density analysis using the imagej program, a free software product available at the National Institutes of Health website. 2 The amount of template RNA, NS5, and incubation time for the RdRP assays were chosen from the linear range of RNA synthesis.…”
Section: In Vitro Rdrp Assaymentioning
confidence: 99%
“…Serological studies revealed a broad distribution of the virus in Africa, West Asia including India, and the Middle East, but only occasionally isolated in Europe, and is thought to be spread by migratory birds (Ref. 2, for reviews, see…”
mentioning
confidence: 99%
“…For example, many arboviruses, including the West Nile £avivirus that was recently introduced into northeastern USA (Lanciotti et al 1999;Rappole et al 2000), are spread over large geographical areas by migratory birds that sometimes concentrate in large groups or are vectored by invertebrates such as mosquitoes that also occur in patchy concentrations. However, studying how vector or host density a¡ects arbovirus infection rates is not usually feasible because groups of hosts or vectors are often transient and not restricted to particular sites that can be systematically sampled.…”
Section: Introductionmentioning
confidence: 99%